2016
DOI: 10.15405/epsbs.2016.07.02.34
|View full text |Cite
|
Sign up to set email alerts
|

Most Relevant Clinical Supervision Strategies In Nursing Practice

Abstract: Clinical supervision (CS) is a facilitator of professional development and quality of practice, promoting safety and protection of clients, through the adoption of targeted strategies. Portugal has been developing research aiming to design policies that support the implementation of CS based on partnerships between academic and practice nurses. This strategy empowers professionals with skills essential for professional development. The study aims to identify the most relevant CS strategies according to nurses'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
0
7
0
7
Order By: Relevance
“…It can be concluded that there is a high level of consensus in the indicators directed to reflexive processes, which is corroborated by some researchers who consider reflexive practice as an integral part of clinical supervision (3)(4) , making it essential to have specific training in this area (16) that includes in its plan strategies for developing the critical-reflexive capacity of the supervisee (17) . Nurses increasingly need to think critically and reflect on their actions to promoting and delivering quality health care so that they can be properly prepared and able to adapt to the constant changes in health contexts.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…It can be concluded that there is a high level of consensus in the indicators directed to reflexive processes, which is corroborated by some researchers who consider reflexive practice as an integral part of clinical supervision (3)(4) , making it essential to have specific training in this area (16) that includes in its plan strategies for developing the critical-reflexive capacity of the supervisee (17) . Nurses increasingly need to think critically and reflect on their actions to promoting and delivering quality health care so that they can be properly prepared and able to adapt to the constant changes in health contexts.…”
Section: Discussionmentioning
confidence: 82%
“…There were 14 strategies for clinical supervision in nursing selected (observation, demonstration, case analysis with the supervisee, feedback, support, critical-reflexive analysis of practices, reflexive report, group supervision sessions, nursing care documentation analysis, continuous training, Individual supervision sessions, self-supervision, group case analysis and distance supervision) identified in the literature and considered as relevant (4) , emerging the indicators for the basis for its construction from this exercise of analysis and exploration of each strategy and its defining characteristics. The questionnaire was analyzed by a group of 14 experts with experience and training in the clinical supervision area and Education Sciences to investigate the content validity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Abd El-Halem [30] and Fulton [31] had clarified the role of training in improving clinical supervision as their study results found a highly statistically significant improvement in nurses managers' supervision competencies and stated that the educational program was effective in improving their clinical supervision. A study conducted by Piresa [8] about most relevant clinical supervision strategies in nursing practice reported that continuing education is grounded on the training framework of clinical supervision and should be delineated in an integrative way in the supervision process, since this is well-thought-out of major relevance to nurses' professional practice. It also leads to the enhancement of skills, encourage self-training, research, innovation, acquisition of skills, competencies and knowledge, and favoring the improvement of self-autonomy.…”
Section: Discussionmentioning
confidence: 99%
“…[7] Clinical supervision facilitates professional development and quality of practice and promotes safety and protection of clients through the adoption of targeted strategies. [8] Nursing supervision is a process intended to improve the learning and performance of another with the direct intention of improving the supervisee's talent to initiate the highest quality of care. Many organizations feel that the most future task of them is clinical supervision.…”
Section: Introductionmentioning
confidence: 99%